Integrating Conservation and Ecotourism within Community-Based Mangrove Management: Empirical Evidence from Sawinggrai, Raja Ampat - Novelina Tampubolon; Novelin Saranga; Yuanike Kaber; Yusril Munawir (Green Insight Solutions, 2026)
Mangrove ecosystems play a crucial role in maintaining coastal stability while supporting local welfare through environmental services and sustainable economic opportunities. In archipelagic regions such as Raja Ampat, integrating mangrove conservation with community-based ecotourism is a strategic necessity; however, this approach often faces complex institutional and governance challenges. A significant research gap remains in understanding how the nuanced interactions among subsystems within the social–ecological system (SES)—specifically the interplay between resource units, governance systems, and actors—determine long-term sustainability. This study addresses this gap by assessing the biophysical status of mangroves and community dynamics in Sawinggrai Village to develop an integrated, community-based management model. Using a qualitative explanatory case study with a participatory approach, data were collected from 50 stakeholders through in-depth interviews, focus group discussions, and field observations. Data were analyzed using an interactive qualitative framework, strengthened by an SES perspective to capture the feedback loops between social and ecological components. The findings reveal that although mangrove ecosystems remain in relatively good biophysical condition with low to moderate anthropogenic pressure, the system’s stability is precarious. Strong customary institutions and high community awareness coexist with limited formal regulatory structures and unequal access to ecotourism benefits. A key contribution of this study lies in demonstrating that inequitable benefit-sharing functions as a critical mediating variable that weakens collective action and, consequently, ecological sustainability. To address this, the study proposes an integrative management model that aligns ecosystem protection, institutional strengthening, and equitable benefit-sharing within a dynamic SES framework. This model advances both theory and practice by offering a scalable approach for reconciling livelihood needs with conservation objectives.